La ‘Umma est-elle une communauté linguistique ? - Chahrazed Dahou (Lengas)
Questioning the concept of “ linguistic community” to better understand the sociolinguistic model of a country, is a fundamental step for Sociolinguists that base their researches on the principles of (Labov 1976), (Bourdieu 1975) and (Boyer 2001-2008). This term may explain the operational mode of language diglossia within a linguistic community, by questioning the attitudes and representations of its speakers. Here, in an Algerian context by questioning the linguistic attitudes of Algerian speakers. It is well known that Algeria is a state where the only official language is "a form of Arabic that has no native speaker" (Chachou 2013,15) and in which, Tamazight is recognized as a national language since 2002. This region in its sociolinguistic complexity includes other languages as well, all of which are actually practiced, yet they have no established political status. French language, which is alternately a colonial language (tongue) and one of, opening on to the world, works paradoxically as both a local and a foreign language at the same time. Algerian dialects seem to be recognized by its speaker as different from standard Arabic, while at the same time being rejected: "This is not a language, it is a mixture”. This unprecise depreciation of the Algerian speaking by the Algerians themselves towards Arabic language, urges us to raise the question as to which definition of linguistic community operates on Algerian ground? In the sense which a linguistic community is a set of people who share a language as well as the representations and attitudes towards the language itself, we pose the question, what are the linguistic attitudes of Algerian speakers? Knowing that Algeria is officially an Arab country; is it possible to explain its sociolinguistic configuration without taking into account the contents of the “Umma” diglossique ideology? While we do not intend to identify all of the functioning mechanism of Umma (where Book, mother and mother (native) language blend), this article tries, through a comprehensive set of investigations about the linguistic attitudes of Algerian speakers, to refresh the often narrow links between linguistic community and religion in Algeria.